Letter from Travers Buxton of the Anti-Slavery and Aborigines' Protection Society to Roger Casement regarding Casement's report and sending it to Sir Fowell Buxton and Noel Buxton, organising an interview with a "Mr. Payne" of the Bolivian Mission and discussing the "Inambari Para-Rubber Company" and "Tambopata Rubber Company" - Anti-slavery and Aborigines Protection Society (Great Britain); Buxton, Travers 1865-1945; Casement, Roger, 1864-1916 (1911)
Informs him of an enclosed copy of "Surrey Comet", please see MS 13,073/45i/21.
Typescript. Letter is typed on "The Anti-Slavery and Aborigines Protection Society / 51, Denison House, / Vauxhall Bridge Road, / London, S.W." headed paper.
Keywords: Casement, Roger, -- 1864-1916 -- Correspondence; Buxton, Thomas Fowell -- Sir -- 1837-1915; Noel-Buxton, Noel Noel-Buxton, -- Baron, -- 1869-1948; Conway, William Martin, -- Sir, -- 1856-1937; Rubber industry and trade -- Amazon River Region -- History -- 20th century; Ireland -- History -- 1910-1921; Amazon River Region -- Description and travel